The Effect of Group Counseling Guidance on Body Image in Adolescent Girls - Agustaria Ginting; Imelda Derang; Indah Gaung S Sibagariang (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2022)
Body image is the person's perceptions, thoughts, and feelings toward his body. Related studies indicate that among the populace, it is often the teenage girls who express feelings of dissatisfaction toward their bodies and are therefore more inclined to have negative body image as is shown in the initial survey result at 61.5 %. Group guidance and counseling are viewed as appropriate interventions to help in this specific problem. This study then aims to determine the effects of group guidance and counseling on the body image of the adolescent girls at SMA Negeri 1 Bandar Trade Simalungun Regency during the Covid-19 Pandemic Period in 2021. One group Pre-test and Post-test design was the experimental method used in the study. From the population of 757 female adolescents, 85 were taken as respondents through the purposive sampling technique. The respondent's data collection was taken through a questionnaire accessible through a google link. The pre-test body image mean score was 25.56 while the post-test body image mean score was 29.75 with each standard deviation score of 4.552 and 4.843 respectively. It can be seen that the difference between the mean score of the first and second measurement is 4.188 and the difference between the standard deviation score is 2.970. Based on the statistical results of the paired samples test, the value p = 0.001 (p < 0.05) signifies that there is a significant effect of group guidance and counseling as treatment on the negative body image of adolescent girls. It is therefore highly recommended that the school conducts regular group guidance and counseling to students on regular basis.